Assessing the sustainability of Arabica coffee-growing householders in the Montanhas do Espírito Santo’ geographic indication region, Brazil: an integrated case study (Research, Society and Development, 2022)
Coffee growing is an important activity for the income of farms and the production of specialty coffees should be encouraged. However, it is necessary that this process respects the principles based on the economic, environmental, and social axes of sustainability. This research was carried out in the municipality of Conceição do Castelo, State of Espírito Santo, Brazil aiming to assess the initial benchmark of the sustainability of three farms. The results showed a gap in the three axes with intervention needs mainly related to economic standards, followed by social and environmental. Different interventions and adaptations need to be used on each farm aiming to reach better levels of adequacy according to sustainability criteria; however, the values of the families and their limitations must be respected, particularly the economic, social, and cultural conditions. The three coffee farms need adjustments for the production of specialty coffees, mainly related to economic criteria. In this way, farms will be able to reach new markets, add value to coffee beans, increase farm income and develop sustainability.